A STUDY ON THE EFFECT OF DIETARY FACTORS ON FUNCTIONAL GASTROINTESTINAL DISORDERS IN WOMEN OF HA’IL REGION IN SAUDI ARABIA - Kundur, Ramadevi; Reddy Lingala, Kalyan Viswanath; Alrshedi, Abeer Rawaf Moayd (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study is to assess the prevalence of functional gastrointestinal disorders (FGIDs) among the women population of the Ha'il region in Saudi Arabia. It also includes the analysis of the effect of dietary factors on FGIDs and to evaluate if any significant correlation exists between the type of diet and FGIDs. Methods: A cross-sectional study was conducted at the Maternity and Children's Hospital and Ha'il General Hospital in the Ha'il Province of Saudi Arabia with 501 random women patients who had visited these hospitals. Data were collected through a questionnaire and analyzed using the statistical program SPSS-21. Results: In this study, 50% of the women population in Ha'il had at least one of the FGIDs. Acidity (14.4%) is the prominent FGID followed by gas (11.8%) and abdominal pain (11.4%). The FGIDs increase with age, irrespective of dietary factors. Gas formation was observed to be significantly correlated with age (p<0.05), and unhealthy diet was highly correlated to acidity (p<0.01) and gas formation (p<0.01). Conclusion: FGIDs were observed to be considerably lower if a healthy diet was maintained at least up to 40 years of age. High fiber and protein-rich diet along with fresh fruits and vegetables are known to reduce FGID symptoms to a great extent; hence, dietary changes along with physical activity could help reduce the occurrence of FGIDs.